COMPETITION AND PROFITABILITY: IMPACT ON STABILITY IN INDONESIAN BANKING - Ivo Nila Krisna; Rida Rahim; Mohamad Fany Alfarisi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
Currently the banking industry has undergone major changes in recent years due to regulatory deregulation. Seeing this, in implementing it, banks must be managed more carefully, one of which is by maintaining it. Banking instability occurs because banks face too many risks. The purpose of this study is to examine how the influence of competition and profitability on banks in the Indonesian banking industry. The population used is commercial banks listed on the Indonesia Stock Exchange in 2015-2019. A series of indicators from internal and external banks are also used in this study to support the research results, which consist of bank size, concentration, inflation, and GDP. That is, banking is measured using three risks, credit risk with NPL proxy, liquidity risk with LDR proxy, and insolvency risk with Z-score proxy. Using panel data analysis, the following results were found in the 2015-2019 research period, competition had a positive and insignificant effect on credit risk, competition had a negative and insignificant effect on liquidity risk and insolvency risk. Profitability has a negative and significant effect on credit risk and insolvency risk, and profitability has a positive and insignificant effect on liquidity risk.